Bringing Doctor‐Patient Medical Decision‐Making into Focus. (July 2014) - Stark, Meredith
Abstract When I finally got eye glasses as a teenager, after denying the need for far too long, I was repeatedly surprised by the world that everyone else had been seeing all along. Leaves on the trees, graffiti by the highway—I was astonished, amazed, and suddenly informed. It is easy to assume we are seeing all we need to see, knowing all we need to know, until something jars us from this false comfort and compels us to reconsider. So it is with thinking about the current state of doctor‐patient decisions. The unfocused view has physicians listening to patients and clearly communicating information about illnesses and treatment options, patients making good use of high‐quality data to craft sound decisions, and doctors joining patient preference with provider beneficence to optimize decisions. The reassuring outlook finds physician paternalism defeated, patients empowered, and all right with the world. Peter Ubel cannot let that fiction stand. In Critical Decisions: How You and Your Doctor Can Make the Right Medical Choices Together, Ubel reminds us that our work in actualizing patient autonomy and fostering patient participation in critical health decisions remains far from over.